Theses - Naujokaitis , P. (Psichologija, 1969)
In Soviet Lithuania the number of scientific workers of pedagogy and other sciences related to it is rapidly growing. Till 1968, 79 theses were maintained (Doctor of Pedagogy - l and Doctor of Philosophy - l; candidates: 55 of Pedagogy, 5 of Philosophy, 2 of Philology, 10 of History, 3 of Biology and 2 of Medicine) in which different problems of pedagogy, psychology, logic and education were dealt with in one or another aspect. 38 theses were maintained in Vilnius, 21 in Moscow, 18 in Leningrad, l in Kyev and l in Tartu.
Keywords: theses; information